Exploring Blood Donation Challenges and Mobilization Mechanisms in North China During the COVID-19 Pandemic: A Qualitative Study - Wang Z; Wang H (Dove Medical Press, 2022)
Zhuo Wang,1,2 Hejian Wang1 1School of Social and Behavioral Sciences, Nanjing University, Nanjing, People's Republic of China; 2The National Police University for Criminal Justice, Hebei, People's Republic of ChinaCorrespondence: Zhuo Wang, School of Social and Behavioral Sciences, Nanjing University, Nanjing, People's Republic of China, Tel +86 15062263226, Email wangzhuo@smail.nju.edu.cnPurpose: The coronavirus disease 2019 (COVID-19) pandemic disrupted the supply of blood globally, resulting in numerous studies focusing on the challenges in maintaining blood supply, and the responses to it, in countries with a mixed blood donation model. This study explored blood donation challenges and mobilization mechanisms in North China, which employs a non-remunerative donation model, during the COVID-19 pandemic's first wave.Materials and Methods: A qualitative approach was adopted to investigate blood donation practices in Chengde from April to June 2020. Data were collected from eight blood donors, six potential donors, three blood donation station leaders, and two government officials, through semi-structured interviews.Results: The major challenge for blood supply was decreased blood donations, owing to lockdown restrictions, and individual and familial apprehensions. Mobilization mechanisms included bureaucratic and ideological mobilization. However, although group blood donation alleviates the pressure on supply chains during emergencies, it is detrimental to the cultivation of civic engagement in the long run.Conclusion: This study contributes to the understanding of how countries with uncompensated blood donation models respond to public health emergencies. It suggests that striking a balance between the society's and the state's perception of blood donation would allow the state to incorporate the different "voices" of society, and devise an inclusive blood donation policy.Keywords: global health, health policy, COVID-19, blood shortage, qualitative research